2021
DOI: 10.1177/00222429211044155
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Social Responsibility on Brand Sales: An Accountability Perspective

Abstract: Consumers are increasingly mindful of corporate social responsibility (CSR) when making purchase and consumption decisions, but evidence of the impact of CSR initiatives on actual purchase decisions is lacking. This article introduces a novel brand accountability–based framework of consumer response to CSR initiatives, which categorizes CSR efforts as “corrective,” “compensating,” or “cultivating goodwill.” Leveraging a database of CSR press releases by leading consumer packaged goods brands, the authors exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 86 publications
2
25
0
Order By: Relevance
“…For example, the shift in the automotive industry from gasoline powered engines to hybrid and electric vehicles is obvious to customers, whereas a service firm's transition to being carbon neutral may not reflect directly in the delivery of the service. This aligns with the findings of Nickerson et al. (2021) showing that firms that are perceived as unsustainable reap larger benefits from ESG efforts.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For example, the shift in the automotive industry from gasoline powered engines to hybrid and electric vehicles is obvious to customers, whereas a service firm's transition to being carbon neutral may not reflect directly in the delivery of the service. This aligns with the findings of Nickerson et al. (2021) showing that firms that are perceived as unsustainable reap larger benefits from ESG efforts.…”
Section: Discussionsupporting
confidence: 89%
“…high firm-cause fit); this increases the effectiveness of ESG communications (Kuo and Rice, 2015). Similarly, ESG efforts with a clear connection to firm operations lead to positive customer outcomes (Nickerson et al. , 2021).…”
Section: Research Agenda For Communicating Esg In Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…It receives around 9 million visitors per year (https://kidzania.com/en). Conversely, other studies concluded that CSR messages can increase positive attitudes towards a brand as well as significantly increase brand purchase intentions (Nickerson et al, 2022;Tai, 2022;Schmeltz, 2011).…”
Section: Dr Maha Misbah Shabanamentioning
confidence: 97%
“…Corporate brands and reputation are essential sources of competitive advantage, which allow firms to attract customers and promote customers’ purchase intention while lowering transaction costs (e.g., Sweetin et al ., 2013). The marketing literature has established that strong CSR engagement helps build a positive brand identity, enhance firm reputations, and achieve a competitive advantage over long periods (e.g., Marin et al ., 2009; Chernev and Blair, 2015; Nickerson et al ., 2021).…”
Section: Esg/csr and Firm Valuementioning
confidence: 99%